Unpacking the Key Drivers of University Students’ Satisfaction and Loyalty Towards Logistics Services in Zhanjiang, China - Zhang, Chao (Scholar: Human Sciences, 2026)
Purpose: This paper investigates the key factors influencing university students’ satisfaction and loyalty in using logistics services in Zhanjiang, China. The conceptual framework presents the causal relationships among operational quality, information quality, personnel contact quality, service ordering procedure, price satisfaction, customer satisfaction, and customer loyalty. Research design, data, and methodology: Researchers used a quantitative approach to administer a survey to 500 students from Zhanjiang University of Science and Technology in China. Non-probability sampling techniques were judgmental sampling, quota sampling, and convenience sampling for data collection. Both online and offline distribution methods were employed to disseminate the questionnaires. Data analysis was conducted using Structural Equation Modeling and Confirmatory Factor Analysis, encompassing model fit, reliability, and structural validity assessments. Results: The findings demonstrate that operational quality, information quality, personnel contact quality, and service ordering procedure exert a significant impact on customer satisfaction, which in turn serves as a mediating variable affecting the relationship between these factors and customer loyalty. Additionally, both price satisfaction and customer satisfaction significantly impact customer loyalty. Among the variables examined, customer satisfaction has the most pronounced effect on customer loyalty, with price satisfaction being the next most influential factor. Conclusions: The statistical data proposes that logistics service providers should increase their investment in factors that influence satisfaction and loyalty and optimize and elevate the quality of these corresponding factors to enhance customer satisfaction and loyalty.